2015
DOI: 10.7322/jhgd.96766
|View full text |Cite
|
Sign up to set email alerts
|

The Act of Playing Within the Hospital Context in the Vision of the Accompanying Persons of the Hospitalised Children

Abstract: Introduction: the infant hospitalisation may put at risk the normal development of the children due to the breaking of their routine and the adjustment to the new reality process. There are several initiatives to promote spaces in hospitals so that the children can have contact with recreational activities. There are many variables that may influence the children's attitude towards the possibility of playful activities, among them the involvement of the accompanying persons. It is essential to learn their inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
(23 reference statements)
0
5
0
3
Order By: Relevance
“…Environments that promote recreational activities are strong allies of motor, emotional, mental and social development, in addition to contributing to a less traumatic hospitalization, as they favor coping with the situation, the (re) significance of pathology and acceptance of treatment (18) . A qualitative approach study with children aged from 7 to 12 years old under outpatient therapeutic follow-up at a pediatric university hospital in Sao Paulo showed that the therapeutic environment, when designed from the perspective of these patients, allows them to know their preferences, as well as their health and disease conditions and treatment, which makes it less traumatic (19) .…”
Section: Introductionmentioning
confidence: 99%
“…Environments that promote recreational activities are strong allies of motor, emotional, mental and social development, in addition to contributing to a less traumatic hospitalization, as they favor coping with the situation, the (re) significance of pathology and acceptance of treatment (18) . A qualitative approach study with children aged from 7 to 12 years old under outpatient therapeutic follow-up at a pediatric university hospital in Sao Paulo showed that the therapeutic environment, when designed from the perspective of these patients, allows them to know their preferences, as well as their health and disease conditions and treatment, which makes it less traumatic (19) .…”
Section: Introductionmentioning
confidence: 99%
“…Assim, o brincar no hospital proporciona, à criança, oportunidades de vivenciar esse novo momento em sua vida, de estar doente e hospitalizada, de forma menos estressante, reduzindo os efeitos negativos da ruptura com seu convívio social, com melhor adaptação durante a internação, o que facilita, ao infante, mais a receptividade, o acolhimento e meios para enfrentar as situações advindas do efeito da hospitalização (8) .…”
Section: Idiscussãounclassified
“…In a study, the parents' perception regarding the use of play during the hospitalization was pointed out in a study, where it was clear that, for parents, it is of great importance, since it promotes the reduction of stress caused by hospitalization, helps the child to become more comfortable with the hospital and the hospital routine and reduces the negative impact of the hospital. 18 The parents' bonding with their hospitalized children is narrowed, as many of the activities can be performed between the same as paintings and the use of toys in general. Through the use of play, a combination of benefits is provided, from the promotion of understanding, participation and communication, such as reduction of stress and fear.…”
Section:  View Of the Companions In Relation To The Play Activitiesmentioning
confidence: 99%